TEACHERS’ PERCEPTION ON THE IMPACT OF ENGLISH ON INDONESIAN LANGUAGE AND CULTURE - Khartha, Aqzhariady; Adisaturrahimi, Andi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This article discusses a study on English teacher perceptions of English as a global language in Indonesia. The goals of this research are to determine whether non-native English teachers in Indonesia recognize the rising role of English in the global world, particularly in Indonesian schools, and to learn how those teachers assess the effects of English on Indonesian language and culture. Five English teachers from various secondary schools took part in this study. Data were collected through an open questionnaire. As a result, all of the participants' comments were consistent, stating that English was indisputably crucial in today's competitive world. They tend to have highly positive perceptions of English as a way of connecting with the international community and supporting Indonesian communicative functions. There is also an amazing unanimity that English can coexist beneficially in this country, even though many people argue that the language has a harmful impact on Indonesian